Combined simultaneous two-phase PIV and interface elevation measurements in stratified gas/liquid pipe flow. (September 2015) - Ayati, A.A.; Kolaas, J.; Jensen, A.; Johnson, G.W.
Highlights: S2P-PIV method was significantly improved since previous paper. Probing method provided quantified sub-regime characterization. 2D-waves are predictable with linear wave theory. Interface flow pattern influences PIV profiles heavily. Abstract: The multiphase flow loop at the University of Oslo has been upgraded with a wave measurement gauge consisting of two conductance probes. Hence, we are able to combine the simultaneous two-phase PIV (S2P-PIV) technique, which was presented in a previous paper, and wave field measurements. This unique combination allows us to investigate the flow dynamics of both phases, e.g. velocity profiles, turbulence profiles, distribution of turbulent structures, as well as the wave statistics, e.g. wave amplitudes and speeds, power spectral densities, of the exact same stratified flow pattern. The present study is the second in a series of two-phase flow experiments aimed both at expanding our understanding of the dominant mechanisms that account for important flow parameters such as the pressure drop and liquid hold-up, as well as providing measurements for the validation of existing two-phase flow models. Some sophisticated models require information about the wave patterns and interfacial turbulence as input parameters and yield, amongst other things, the velocity distribution as an output parameter. The latter can therefore be compared to measured velocity profiles once the wave statistics for the same flow pattern have been inserted as input parameters.